Correction: Synthesis, spectroscopic characterization, X-ray structure and electrochemistry of new bis(1, 2-diaminocyclohexane)gold(iii) chloride compounds and their anticancer activities against PC3 and SGC7901 cancer cell lines. (2nd July 2020) - Al-Jaroudi, Said S.; Monim-ul-Mehboob, M.; Altaf, Muhammad; Fettouhi, Mohammed; Wazeer, Mohammed I. M.; Altuwaijri, Saleh; Isab, Anvarhusein A.
Abstract : Correction for 'Synthesis, spectroscopic characterization, X-ray structure and electrochemistry of new bis(1, 2-diaminocyclohexane)gold(iii ) chloride compounds and their anticancer activities against PC3 and SGC7901 cancer cell lines' by Said S. Al-Jaroudi et al., New J. Chem., 2014, 38, 3199–3211, DOI: ; 10.1039/C3NJ01624B .